1999
DOI: 10.1039/a809293a
|View full text |Cite
|
Sign up to set email alerts
|

Supported nickel catalysts: Preparation and characterisation of alumina-, molybdena-, and silica-supported nickel, and the identification of reactive oxygen on these catalysts by exchange with isotopically labelled carbon dioxide

Abstract: Nickel catalysts, supported on alumina, silica, and molybdena, have been prepared by impregnation and co-crystallization. In the precursor state the catalysts were characterised by UVÈvisible spectroscopy, thermogravimetric analysis/di †erential thermal analysis (TGA/DTA), and X-ray photoelectron spectroscopy (XPS). The nickel was principally in the 2] oxidation state with an octahedral coordination. However, the ligand sphere surrounding the nickel ion was sensitive to the support, indicating that the species… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…However, there is no general consensus on the extent and variation of the interaction of Ni atoms as the Si/Al ratio of the support is varied. The reported conclusions vary between the reducibility of Ni being greater over Al 2 O 3 than over SiO 2 (Turlier et al 1985;Guimon et al 2000), being greater over SiO 2 than over Al 2 O 3 (Kirumakki et al 2006;Amblard et al 1999) or to a similar reducibility over both Al 2 O 3 and SiO 2 (Jackson et al 1999). Whereas the reduction of unsupported NiO has been reported at 220 o C (Li and Chen 1995) or 200 o C (Zielinski 1997), the reduction of NiO that displays no support interaction has been reported as occurring at a slightly higher temperature (Tsonchevaa et al 2005;Xu and Wang 2005).…”
Section: Tpr Studiesmentioning
confidence: 91%
See 1 more Smart Citation
“…However, there is no general consensus on the extent and variation of the interaction of Ni atoms as the Si/Al ratio of the support is varied. The reported conclusions vary between the reducibility of Ni being greater over Al 2 O 3 than over SiO 2 (Turlier et al 1985;Guimon et al 2000), being greater over SiO 2 than over Al 2 O 3 (Kirumakki et al 2006;Amblard et al 1999) or to a similar reducibility over both Al 2 O 3 and SiO 2 (Jackson et al 1999). Whereas the reduction of unsupported NiO has been reported at 220 o C (Li and Chen 1995) or 200 o C (Zielinski 1997), the reduction of NiO that displays no support interaction has been reported as occurring at a slightly higher temperature (Tsonchevaa et al 2005;Xu and Wang 2005).…”
Section: Tpr Studiesmentioning
confidence: 91%
“…The stronger the metal-support interaction, the higher the reduction temperature of the metal oxide. There are reports in the literature of metal-support interactions for Ni catalysts supported on SiO 2 /Al 2 O 3 (Kirumakki et al 2006;Xu et al 2001;Turlier et al 1985;Amblard et al 1999;Jackson et al 1999;Guimon et al 2000). However, there is no general consensus on the extent and variation of the interaction of Ni atoms as the Si/Al ratio of the support is varied.…”
Section: Tpr Studiesmentioning
confidence: 99%
“…Compared to other noble metals, the catalytic performance of Ni is substantially higher for H 2 and CH 4 production through hydrogenation and methanation reactions, respectively [23,52,53,55] . Several catalyst supports investigated for Ni impregnation are alumina, silica, molybdenum [60] , olivine [61] , graphite [62] and lignocellulosic biomass [55] . However, the present study systematically demonstrated the effective impregnation of Ni onto activate carbon support and its application in SCW gasification of complex petrochemical wastes such as petcoke and asphaltene.…”
Section: Gasification Conditionsmentioning
confidence: 99%
“…One of the most common hydrogenation catalyst formulation is nickel on oxidic (e.g., alumina, zirconia, ceria, titania, or silica) [55,63,64] or carbon [65,66] supports. As mentioned above, such catalysts are normally used as methanization catalysts, and other applications are also in common use such as catalysts, for example, for hardening of oils and fats in food industry, dry reforming of methane to manufacture syngas by using CO 2 [67,68], or in petrochemical industries and refinery.…”
Section: Catalytic Properties Of Supported Metal Nanoparticlesmentioning
confidence: 99%